2021
DOI: 10.1088/1361-6641/ac1312
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of in situ CNT/WO3∙H2O nanoplate composites for adsorption and photocatalytic applications under visible light irradiation

Abstract: Composites of refluxed carbon nanotubes (CNTs) at different contents and orthorhombic tungsten oxide hydrate (WO 3 •H 2 O) were prepared via acid precipitation at room temperature. The CNTs produced a new phase of monoclinic tungsten oxide dihydrate WO 3 •2H 2 O, caused the breakage of WO 3 •H 2 O nanoplates, and affected the microstrain in the nanocomposites. The CNTs also enhanced the absorbance in the visible range and increased the specific surface area and pore volume but abnormally enlarged the optical b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The isotherm analysis showed that the sample had a specific surface area of 53.3 m 2 g −1 and a bimodal pore size distribution with an average pore size of 5.5 nm. Notably, the obtained specific area is large in comparison with other works based on WO 3 and carbon-based nanocomposites [14][15][16][17]. These properties are preferable for surface area-driven applications such as photocatalyst, and pathogen controlling.…”
Section: Fesem and Bet Analysismentioning
confidence: 91%
See 1 more Smart Citation
“…The isotherm analysis showed that the sample had a specific surface area of 53.3 m 2 g −1 and a bimodal pore size distribution with an average pore size of 5.5 nm. Notably, the obtained specific area is large in comparison with other works based on WO 3 and carbon-based nanocomposites [14][15][16][17]. These properties are preferable for surface area-driven applications such as photocatalyst, and pathogen controlling.…”
Section: Fesem and Bet Analysismentioning
confidence: 91%
“…In these alternatives, compositing with 2D carbon-based materials like graphene (Gr) or graphene oxide (GO) shows a high potential for enhancing photo-electrochemical and photocatalytic activity [12][13][14][15][16]. To controllably and simply prepare uniform metal oxide-based nanocomposites, wet chemical-based methods like reduced agglomeration [5], precipitation method [9,17], and hydrothermal method [6][7][8]16], etc are the most widely used methods, in which hydrothermal method shows the most prominent potential [6][7][8]16].…”
Section: Introductionmentioning
confidence: 99%
“…3 presented Raman spectra of all samples, which implied the change of samples' phase with the reaction temperature. In sample RT's Raman spectrum, the characteristic peaks of both monoclinic WO 3 • 2H 2 O and orthorhombic WO 3 •H 2 O were observed at 658, 945, and 956 cm −1 [30][31][32]. In Raman spectra of sample T100, only characteristic peak of orthorhombic WO 3 •H 2 O appeared, but in Raman spectra of samples T120, T150, and T180, the characteristic peaks of both orthorhombic WO 3 •H 2 O (at 638 and 945 cm −1 ) and monoclinic WO 3 (at ∼ 711 and 806 cm −1 ) were observed [16][17][18].…”
Section: Iii3 Raman Analysismentioning
confidence: 99%
“…In recent decades, nanoscience and nanotechnology have been directed to the carbon nanostructures (graphene, diamond, nanotubes, and nanowires, etc.) due to their fascinating physical properties as well as their potential application in nanoelectronics. With the discovery of graphene, other allotropes of carbon were also discovered and carbon nanotubes (CNTs) was one of them which was first discovered in 1991 . One dimensional (1D) single-walled carbon nanotubes (SWCNTs) have become a focal point for many researchers with the hope of constructing nanomechanical sensors, nanoelectronics and optoelectronic devices. Many researchers have conducted extensive experimental and theoretical research on it. Structurally, like in graphene, C–C bonds are formed by sp 2 bonding in CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…due to their fascinating physical properties 1 4 as well as their potential application in nanoelectronics. 5 8 With the discovery of graphene, 9 other allotropes of carbon were also discovered and carbon nanotubes (CNTs) was one of them which was first discovered in 1991. 10 One dimensional (1D) single-walled carbon nanotubes (SWCNTs) have become a focal point for many researchers with the hope of constructing nanomechanical sensors, nanoelectronics and optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%